PENGARUH KINERJA KEUANGAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (Studi Empiris pada Perusahaan Barang Konsumen Primer yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Muhammad Hikmal Alfath; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2026)
This study examines the influence of profitability, liquidity, leverage, and dividend policy on firm value in Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange during the 2021–2023 period. Signaling theory and pecking order theory are used as the conceptual basis of the research. A purposive sampling technique was applied, resulting in 132 firm-year observations. The data were analyzed using multiple linear regression. The results show that profitability and dividend policy positively and significantly affect firm value, while liquidity has a negative and significant impact. Meanwhile, leverage is found to have no significant effect on firm value. These findings suggest that investors place more importance on earnings performance and dividend distribution as primary indicators for assessing firm value.